Pain quotidien d’un lexicographe ou la description lexicographique du vocabulaire de la nourriture selon l’approche orientée objets - Chrupała, Aleksandra (Neophilologica, 2008)
The aim of this article is to describe the object-oriented method with its application to a given description. Basing on the noun pain the author describes some difficulties that might be found in the lexicographic description of the object class <bread>. The main objective is to make a distinction between a typical predicate and the one inherited by the class, to classify operators into constructors, manipulators and accessors, and finally to distinguish each domain belonging to the given class. Moreover, the author raises the issue of translation; namely the necessity of giving one equivalent as well as the consequences of such a requirement.